Predictors and Prognostic Implications of Major Adverse Cardiovascular Events after Renal Transplant: 10 Years Outcomes in 321 Patients - Aftab, Waqas; Varadarajan, Padmini; Rasool, Shuja; Pai, Ramdas G. (International Journal of Angiology, 2014)
Renal transplantation is the treatment of choice in patients with end-stage renal disease. Major adverse cardiac events (MACE) are common after renal transplant, especially in the perioperative period, leading to excess morbidity and mortality. The predictors and long-term prognostic implications of MACE are poorly understood. We analyzed predictors and implications of MACE in a cohort of 321 consecutive adult patients, who received renal allograft transplantation between 1995 and 2003 at our institution. The characteristics of 321 patients were: age at transplant 44 ± 13 years, 60% male, 36% diabetes mellitus (DM), left ventricular ejection fraction (LVEF) 60 ± 16%. MACE occurred in 21 patients with cumulative rate of 6.5% over 3 years after renal transplant, 57% occurring within 30 days, 67% within 90 days, and 86% within 180 days. MACE was not predicted by any clinical or pharmacological variables including age, gender, hypertension, DM, prior myocardial infarction, smoking, duration of dialysis, LVEF, or therapy with β-blockers (BB), angiotensin converting enzyme inhibitors, or calcium channel blockers. However, a clinical decision to perform a stress test or a coronary angiogram was predictive of higher MACE rate. MACE, irrespective of type, was independently associated with higher mortality over a period up to 15 years and this seemed to be blunted by BB therapy. MACE rate after renal transplantation decreases over time, most occurring in the first 90 days and is not predicted by any of the traditional risk factors or drug therapies. It is associated with higher long-term mortality.
Keywords: end-stage renal disease; survival; major adverse cardiac events